2010
DOI: 10.1631/jzus.b1000079
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interrupted endogenous BMP/Smad signaling on growth and steroidogenesis of porcine granulosa cells

Abstract: Bone morphogenetic proteins (BMPs) play a critical role in the growth and steroidogenesis of granulosa cells (GCs). BMP signals act through membrane-bound heteromeric serine/threonine kinase receptors. Upon ligand binding, BMPs activate intracellular Smad proteins and regulate growth and apoptosis in various cell types. The objective of this study was to demonstrate the effects of BMP/Smad signal on growth and steroidogenesis of porcine GCs. A strategy of RNA interference (RNAi)-mediated 'gene silencing' of Sm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 31 publications
(33 reference statements)
0
9
0
Order By: Relevance
“…4 and Supplementary Table S6), were also induced by silencing of SMAD4, strongly suggesting that silencing of SMAD4 promoted cell cycle in porcine follicular GCs. In the previous study, interrupted SMAD4 enhanced apoptosis levels by reducing the expression of BCL2 but not BAX in porcine GCs (Wang et al 2010c). Moreover, our recent data also showed SMAD4-sliencing promoted the rate of apoptosis in porcine follicular GCs and downregulated the anti-apoptotic genes of BCL2 instead of BAX (Liu et al 2014).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…4 and Supplementary Table S6), were also induced by silencing of SMAD4, strongly suggesting that silencing of SMAD4 promoted cell cycle in porcine follicular GCs. In the previous study, interrupted SMAD4 enhanced apoptosis levels by reducing the expression of BCL2 but not BAX in porcine GCs (Wang et al 2010c). Moreover, our recent data also showed SMAD4-sliencing promoted the rate of apoptosis in porcine follicular GCs and downregulated the anti-apoptotic genes of BCL2 instead of BAX (Liu et al 2014).…”
Section: Discussionmentioning
confidence: 59%
“…In fact, the role of SMAD4 gene in steroidogenesis is still controversial. In ovarian-specific Smad4-knockout mouse GCs, Smad4 loss increased the expression levels of STAR, Cyp11a1, Hsd3b1, and Hsd17b7 and resulted in disrupting regulation of steroidogenesis (Pangas et al 2006), but SMAD4 knockdown in porcine GCs was shown to downregulate the expression levels of CYP19A1 and HSD3B, without any significant changes in expressions of CYP11A1 and STAR genes (Wang et al 2010c(Wang et al , 2011. In the present study, upregulated expressions of HSD3B1 and STAR under SMAD4-silencing were consistent with the results discovered by Pangas et al (2006), indicating SMAD4-silencing might enhance the synthesis of steroid.…”
Section: Discussionmentioning
confidence: 92%
“…In mammals, SMAD4 is the only co‐mediating Smad; it translocates to the nucleus with phosphorylated R‐Smads and subsequently modulates the transcription of BMP target genes (Wang et al. ). Smad complexes regulate many biological processes, including cell proliferation, differentiation and apoptosis during embryonic development, as well as adult tissue homoeostasis (Costello et al.…”
Section: Discussionmentioning
confidence: 99%
“…Interrupted BMP/Smad signalling pathway through SMAD4 significantly inhibited the growth of granulosa cells (Wang et al. , ) and decreased the estradiol production and the steroidogenic enzymes (CYP19a1 and CYP11a1) mRNA expression (Wang et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Folliculogenesis in mammals is a complex process involving a series of sequential steps in which a growing follicle either develops to the ovulation stage or undergoes atresia (Wang et al, 2010). The normal maturation process of the chicken oocyte within the ovarian follicle depends on the coordinated development of follicular wall inducing granulosa and/or theca cells under the influences of various hormones and growth factors.…”
Section: Introductionmentioning
confidence: 99%